Pan-Arctic collaborative for eHealth : need, value, lessons - Scott, R.E.; Khoja, S.; Durrani, H. (PAN Asian Collaboration for Evidence-based eHealth Adoption and Application (PANACeA), Karachi, PK, 2009)
This one-pager advocates for a networked research approach modelled on the PAN Asian Collaboration for Evidence-based e-Health Adoption and Application (PANACeA), that focuses on eHealth implementation in the Arctic. The benefits of networked research activities include a broader sharing of knowledge, increased scope for research activities, greater capacity building, and administrative resilience. Yet no Arctic focused eHealth research network exists. As well, the International Journal of Circumpolar Health shows only sporadic and low ehealth publication.